Comparative studies of poly(€-caprolactone) and poly(D,L-lactide) as core materials of polymeric micelles - Man Theerasilp (2018)
Polymeric micelles have been successfully used to deliver a variety of therapeutic agents. Nonetheless, several limitations and considerations must be clarified and well-studied to achieve the highest therapeutic effect. In this study, a series of methoxy poly(ethylene glycol)-block-poly(ε-caprolactone) (PEG-b-PCL) and methoxy poly(ethylene glycol)-block-poly(D,L-lactide) (PEG-b-PLA) with varying molecular weight (MW) of hydrophobic core segment were synthesized. These block copolymers can form micelle with PCL or PLA as core-forming blocks and PEG as a coronal material. The effect of MW on micelle size and critical micelle concentration (CMC) was studied. DOX (DOX) was encapsulated inside the micelle core. Drug-loading content and size of micelles were studied. Drug release studies inside cells were evaluated by confocal laser scanning microscopy. In summary, the PLA core which is less hydrophobic than PCL showed higher CMC, smaller micelle size and faster DOX release inside nucleus. © 2013 Informa UK Ltd.